ANALISIS PEMBELAJARAN AKTIF DENGAN PENDEKATAN COLLABORATIVE LEARNING PADA MATA KULIAH MANAJEMEN PENDIDIKAN DI STAIN KUDUS - Akbar, Rofiq Faudy (Pascasarjana IAIN Kudus, 2013)
This article is the result of an evaluative study of learning in management education courses. Sample of this research were 33of whom are students majoring Tarbiyah PAI 7th semester. Overallrespondents aged between 20-21 years with sex characteristics ofmen amounted to 13 people (40%), female about 20 people (60%).By using survey methods, this study aims to gather information fromstudents as learners regarding the application of the principles ofactive learning collaborative in Education Management courses.The results showed that the implementation of learning has been inline with expectations. The students enjoy and feel happy or fit withthe implementation of the learning model.